What are the risks of surgical adverse outcomes in newborn boys undergoing circumcision?. Issue 6 (June 2018) - Ericson, Kevin; Neumann, Theodore; Seger, Theodore; Walsh, Patrick
Abstract : EVIDENCE‐BASED ANSWER : The overall rate of complications with newborn circumcision is low, ranging between 0% and 3%, although the rate of complications is as high as 16% in some settings around the world. Serious complications, including partial amputation of the glans and urethral laceration, occur in 0% to 2% of circumcisions (SOR: C, systematic review of case series and single case series). Meatal stenosis can be a late complication and is associated with 2.7% of circumcisions (SOR: C, casecontrol study).